Psychological Conflict Of The Main Character Portrayed In Sam Levinson’s Movie Series: Euphoria - Sinaga, Gusnida Rezeky; Saragih, Amrin (TRANSFORM : Journal of English Language Teaching and Learning, 2023)
This study is concerned with Psychological conflicts experienced by the main character in Sam Levinson's movie series "Euphoria." This study used descriptive qualitative to explore the kinds of psychological conflicts experienced by the main character in Euphoria. This study used Sigmund Freud’s (1923) psychoanalysis theory to examined the data in this study. The results of the data were found that (1) There were three kinds of psychological conflict experienced by the main character, namely Id, Ego, and Superego. (2) There were three factors that caused psychological conflict, namely losing the father, mis understanding, and uncomfortable situations. (3) There were four ways how the main character overcame the psychological conflict such as, sublimation, repression, and denial. In conclusion, the dominant psychological conflict experienced by the main character is the Id aspect.